A systematic review of treatments for settling problems and night waking in young children. Issue 7229 (22nd January 2000) - Ramchandani, Paul; Wiggs, Luci; Webb, Vicky; Stores, Gregory
Abstract: Objectives: To assess the efficacy of treatments for settling problems and night waking in young children. Design: A systematic review of randomised controlled trials of interventions for settling problems and night waking in young children. Setting: Electronic bibliographic databases and references on identified papers, hand searches, and personal contact with specialists. Subjects: Children aged 5 years or less who had established settling problems or night waking. Interventions: Interventions had to be described and a placebo, waiting list, or another intervention needed to have been used as a comparison. Interventions comprised drug trials or non-drug trials. Main outcome measures: Number of wakes at night, time to settle, or number of nights in which these problems occurred. Results: Drugs seemed to be effective in treating night waking in the short term, but long term efficacy was questionable. In contrast, specific behavioural interventions showed both short term efficacy and possible longer term effects for dealing with settling problems and night waking. Conclusions: Given the prevalence and persistence of childhood sleep problems and the effects they can have on children and families, treatments that offer long lasting benefits are appealing and these are likely to be behavioural interventions.